2016
DOI: 10.3389/fpls.2016.01976
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sucrose in the Hypocotyls of Radish Sprouts Contributes to Nitrogen Deficiency-Induced Anthocyanin Accumulation

Abstract: Effects of nitrogen (N) deficiency and sucrose (Suc) addition on regulation of anthocyanin biosynthesis and their relationship were investigated in this study. Radish sprouts subjected to N deficiency had 50% higher anthocyanin accumulation than when grown in Hoagland solution (a nutrient medium with all macronutrients). The contents of endogenous soluble sugars (Suc, fructose, and glucose) in the hypocotyls were also markedly increased by N limitation, with Suc showing the highest increase. Inhibition of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
(55 reference statements)
0
29
0
Order By: Relevance
“…In particular, low nitrogen availability has been shown to significantly increase the accumulation of phenolic compounds by regulating the expression of major enzymes related to phenolic biosynthesis and positive and negative transcription factors, such as MYBs. 8,12,13 We have previously shown that cultivation under low nitrogen conditions increases the transcriptional levels of genes or enzyme activities related to the phenolic synthesis pathway in lettuce, resulting in higher phenolic accumulation. [14][15][16] Interestingly, reduction of nitrogen supply may also have human and environmental benefits through decreasing the nitrate accumulation in vegetables and limiting nitrogen loss in the environment, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, low nitrogen availability has been shown to significantly increase the accumulation of phenolic compounds by regulating the expression of major enzymes related to phenolic biosynthesis and positive and negative transcription factors, such as MYBs. 8,12,13 We have previously shown that cultivation under low nitrogen conditions increases the transcriptional levels of genes or enzyme activities related to the phenolic synthesis pathway in lettuce, resulting in higher phenolic accumulation. [14][15][16] Interestingly, reduction of nitrogen supply may also have human and environmental benefits through decreasing the nitrate accumulation in vegetables and limiting nitrogen loss in the environment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Several studies have found that the foliar or root application of Suc can significantly increase the accumulation of phenolic compounds in plants, which was linked to changes in the expression of genes involved in phenolic biosynthesis. 12,[20][21][22] Interestingly, increased Suc production has frequently been observed in plants grown in low-nitrogen conditions. 12,[23][24][25] Taken together, these results suggest that Suc may play an important role in regulating the low-nitrogeninduced accumulation of phenolic compounds in vegetables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…positively regulates anthocyanin structural genes (Wan, Zhang, Song, Tian, & Yao, ). In the hypocotyls of Raphanus sativus , an increase in the level of soluble sugars, especially sucrose, contributes to an accumulation of anthocyanin that results from an N‐deficit (Su, Wu, & Jin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen deficiency impairs plant growth, whereas photosynthesis may still occur at a relatively high rate. For example, sugar accumulation was reported for barley leaves (Wang and Tillberg, 1996), barley seedlings (Comadira et al, 2015), and radish hypocotyls (Su et al, 2016) under N deficiency. Also phosphorus, potassium, and magnesium deficiencies were found to result in Suc accumulation in leaves, in parallel with a decrease of this sugar in phloem, which is indicative of growth impairment (Marschner et al, 1996).…”
Section: Variation In Sugar Levels In Plants Under Abiotic Stressmentioning
confidence: 99%